The impact of transformational leadership on the strategic success – An applied in universities in the North sector of Jordan – - Al-Zoubi, Khalid Yosuf; Al-Sharairi, Mutasim Abdullah; Khasawneh, Maen Yousef (Journal of Economic, Administrative and Legal Sciences, 2021)
The study was aimed to identify the impact of transformational leadership on the strategic success in a university in the North sector of Jordan. A questionnaire was developed as a main tool for collection data. Sample was selected by proportional stratified. The study used descriptive and descriptive statistical methods to analyze their data. The study found the level of application of transformational leadership and the strategic success came a medium degree. And there is a statistically significant impact on the level of transformational leadership in the strategic success, and it was explained (%67) of the variation in the strategic success. The study recommends the necessity to encouraging leaders in universities to continue practicing the application of the transformational leadership style because of its advantages and impact on the effectiveness of universities through adopting policies and systems that work on renewed and continuous improvement, and increasing attention to social and human aspects that motivate and motivate workers.
Keywords: transformational leadership; strategic success; universities operating in the northern region of Jordan